2016
DOI: 10.1155/2016/9236573
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs for Fertility Restoration of Different Cytoplasmic Male Sterility Types in Rice Using Two Oryza sativa ×O. rufipogon Backcross Inbred Line Populations

Abstract: Hybrid rice breeding using cytoplasmic male sterility/fertility restoration (CMS/Rf) systems plays an important role in ensuring global food security. Two backcross inbred line (BIL) populations derived from either Xieqingzao B (XB)//XB/Dongxiang wild rice (DWR) (XXD) or XB//DWR/XB (XDX) were used to detect quantitative trait loci (QTLs) for fertility restoration of Dwarf wild abortive- (DA-), Indonesia Paddy- (ID-), and DWR-type CMS in rice. Lines with ID- and DA-type CMS were testcrossed with both the XXD- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…qRf1 partially coincides with a fertility restoration QTL reported by Li et al [42], encompassing the Rf3 position of CMS-WA-type [16,24]. qRf10.1 was reported by Li and Hu [32,45], and it aligns with the CMS-WA-type Rf3 documented by Yao et al [46]. qRf10.2 concurs with the fertility QTL intervals from Li et al [42] and Hu et al [32], as well as with the qRf10 interval of the CMS-DA type identified by Xie et al [33], which is also involved in the recovery of the CMS-WA type of fertility [22,28,47].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…qRf1 partially coincides with a fertility restoration QTL reported by Li et al [42], encompassing the Rf3 position of CMS-WA-type [16,24]. qRf10.1 was reported by Li and Hu [32,45], and it aligns with the CMS-WA-type Rf3 documented by Yao et al [46]. qRf10.2 concurs with the fertility QTL intervals from Li et al [42] and Hu et al [32], as well as with the qRf10 interval of the CMS-DA type identified by Xie et al [33], which is also involved in the recovery of the CMS-WA type of fertility [22,28,47].…”
Section: Discussionsupporting
confidence: 76%
“…The effects were cumulative and influenced by minor genes. Eight QTLs for restoring fertility in CMS-DA-type cytoplasmic sterility have been located on chromosomes 1, 5, 9, and 10 [32][33][34]. These QTLs were mainly on chromosomes 1 and 10, contributing between 2.9% and 43.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular mapping of the Rf genes provides a powerful tool to develop restorer lines avoiding extensive test crossing with CMS lines (Hu et al 2016). Molecular tagging of the fertility restorer gene will help in its transfer to other desirable agronomic background without involving a sterile cytoplasm or extensive test crossing with CMS lines.…”
Section: Introductionmentioning
confidence: 99%
“…Among the cultivated species, high yielding O. sativa grew widely across the globe and low yielding African Rice O. glaberrima is endemic to West Africa. Despite their inferior plant type, seed shattering, poor yield and grain parameters, wild species are rich reservoirs of a novel genes/QTLs for traits like resistance to various biotic stresses (Bhasin et al., 2012; Dong et al., 2020; Ikeda et al., 1990; Khush et al., 1990; Zhang et al., 2000; Sarao et al., 2016; Yang et al., 2020), tolerance to abiotic stresses (Brar & Khush, 2006; Cao et al., 2020; Lei et al., 2013; Luo et al., 2016; Zhang et al., 2017), economically important traits like grain yield (Balakrishnan et al., 2020; Gaikwad et al., 2014; Luo et al., 2011; Xiao et al., 1996), grain quality (Gaikwad et al., 2018; He et al., 2017; Qi et al., 2018), cytoplasmic male sterility (Hu et al., 2016; Zebing & Yingguo, 1988), fertility restoration (Gaikwad et al., 2014) and heterosis for yield contributing traits (Xiao et al, 1998…”
Section: Introductionmentioning
confidence: 99%
“…Elite parental lines can be improved for yield using favourable genes from wild/related species. This species has contributed fertility restorer genes for various CMS systems in cultivated rice (Hu et al., 2016). The identification of yield‐enhancing genes/QTLs from wild rice and introducing them into parents of hybrid rice would dramatically enhance heterosis in rice hybrids (Wu, 2009; Xiao et al., 1996).…”
Section: Introductionmentioning
confidence: 99%